A note on delay robustness for homogeneous systems with negative degree. (May 2017) - Zimenko, Konstantin; Efimov, Denis; Polyakov, Andrey; Perruquetti, Wilfrid
Abstract: Robustness with respect to delays is discussed for homogeneous systems with negative degree. It is shown that if homogeneous system with negative degree is globally asymptotically stable at the origin in the delay-free case then the system is globally asymptotically stable with respect to a compact set containing the origin independently of delay. The possibility of applying the result for local analysis of stability for not necessary homogeneous systems is analyzed. The theoretical results are supported by numerical examples.